Effects of paternal diet and antioxidant addition to the semen extender on bovine semen characteristics and on the phenotype of the resulting embryo - Bastos, Natália Marins [UNESP]; Rossi, Guilherme Fazan [UNESP]; da Silva Leão, Beatriz Caetano [UNESP]; Negrão, Fernanda; Ferreira, Christina Ramires; Vrisman, Dayane Priscila [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Zorzetto, Mariana Furtado; de Paula Freitas-Dell'Aqua, Camila [UNESP]; Vantini, Roberta [UNESP]; Monteiro, Fabio Morato [UNESP]; Mercadante, Maria Eugênia Zerlotti; et al. (Elsevier, 2021)
The aim of this study was to examine the effects of long-term dietary supplementation of young Nellore bulls with rumen-protected polyunsaturated fatty acids (PUFAs) and of the inclusion of catalase in the semen extender on semen quality, in vitro sperm fertilizing ability, and intracytoplasmic lipid content in the resulting embryos. Twelve Nellore bulls were supplemented with rumen-protected PUFAs or with a basal diet from 14 to 24 months of age. The semen was collected at the end of supplementation. For cryopreservation, the ejaculate was divided into two equal volumes and catalase was added to the extender in one of the fractions. Thus, the experimental design consisted of a 2 × 2 factorial scheme with two diets (control and PUFA) and two extenders (Cat+ and Cat-). Total motility and the percentage of rapid cells in fresh semen were negatively affected by dietary supplementation with PUFAs (P < 0.05), but these effects did not persist after freezing. The frozen/thawed semen of animals fed PUFAs exhibited an increase in the percentages of damaged plasma and acrosomal membranes, as well as an increase in the proportion of lipids ions at m/z 578 and m/z 757 detected by MALDI-MS. Nevertheless, there was no effect of the treatments on in vitro embryo development. However, embryos derived from bulls supplemented with PUFAs exhibited higher lipid accumulation compared to control (P < 0.05). In conclusion, PUFA supplementation promoted worsening of semen quality without affecting the in vitro sperm fertilizing ability; however, the paternal diet affected the intracytoplasmic lipid content in the resulting embryos.
Keywords: Bull; Lipid; Nongenetic inheritance; Nutrition; Paternal effect; Polyunsaturated fatty acids